Pengaruh Locus Of Control, Love Of Money, Dan Tingkat Pengetahuan Akuntansi Terhadap Persepsi Etis Mahasiswa Akuntansi Mengenai Creative Accounting - Fajri, Nur Ulya; Zanaria, Yulita; suyanto, suyanto (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the effect of Locus of Control, Love of Money, and Accounting Knowledge Level on Accounting Students' Ethical Perceptions of Creative Accounting and the influence of Locus of Control, Love of Money, and Accounting Knowledge Levels jointly on Accounting Students' Ethical Perceptions of Creative Accounting. Sampling of 118 with research data collection techniques was carried out through a questionnaire. The research data was processed using SPSS version 26. The data analysis technique used multiple linear regression analysis and hypothesis testing. The results of this study indicate that: (1) Locus of Control influences Accounting Students' Ethical Perceptions about Creative Accounting, (2) Love of Money influences Accounting Students' Ethical Perceptions about Creative Accounting, (3) Accounting Knowledge Level influences Accounting Students' Ethical Perceptions regarding Creative Accounting, and Locus of Control, Love of Money, and Level of Accounting Knowledge simultaneously influence the Ethical Perceptions of Accounting Students regarding Creative Accounting.